A Comparison of All-Cause Mortality in Patients Who Required Glaucoma Surgery for Neovascular Glaucoma or Primary Open-Angle Glaucoma: A Retrospective Cohort Study - Laura D. Palmer; Levi D. Kauffman; Gregory B. Russell; Atalie C. Thompson; Gillian G. Treadwell (Vision)
This retrospective review examines whether there is a difference in all-cause mortality in patients who required surgical intervention for neovascular glaucoma (NVG, N = 186) versus primary open-angle glaucoma (POAG, N = 190). Cox proportional hazard models compared mortality across three models: unadjusted, age-adjusted (Model 1), and age-, hypertension-, and diabetes-adjusted (Model 2). In all models, NVG patients who required glaucoma surgery had a higher all-cause mortality rate compared to those with POAG who underwent similar procedures: unadjusted (HR 2.22, (1.59, 3.10), p < 0.0001), Model 1 (HR 2.99, 95% CI (2.12, 4.22), p < 0.0001), and Model 2 (HR 1.88, 95% CI (1.27, 2.80), p < 0.0018). In Model 1, those with NVG due to PDR had a higher all-cause mortality rate after glaucoma surgery than those with NVG secondary to CRVO (HR 2.00, 95% CI (1.19, 3.45), p < 0.0095). Patients treated with CPC had higher all-cause mortality rates than those treated with tube shunt in all models: unadjusted (HR 1.82, 95% CI (1.33, 2.47), p < 0.0001), Model 1 (HR 1.91, 95% CI (1.40, 2.61), p < 0.0001), and Model 2 (HR 1.50, 95% CI (1.04, 2.16), p < 0.03). We observed a higher all-cause mortality rate among patients with NVG requiring glaucoma surgery compared to those with POAG requiring similar surgeries, which could suggest that NVG patients requiring glaucoma surgery had more compromised systemic health.